Double Intussusception in a child presenting as Acute Abdomen- A case report.: A Case of Double Intussusception in a child - BISTA, CHIRAN BHAKTA; Raman, V Shankar; Nair, Vipin V; Singh, Vivek Kumar; Rehsi, Simarjit Singh; Sengupta, Prashant (Iranian Journal of Pediatric Surgery, 2024)
Double intussusception in children is an extremely rare entity with only 15 cases reported in medical literature till present. An 18-month-old male child presented with features of intestinal obstruction. Evaluation showed an ileocolic intussusception on ultrasound. Initially, hydrostatic pressure reduction was attempted but was unsuccessful. Exploratory laparotomy revealed a double intussusception of ileo-ileal intussusception over colon and Meckel’s diverticulum as the lead point. The histopathology of the excised specimen revealed normal ileum and hypertrophic pancreatic tissue in the Meckel’s diverticulum. The significance of early diagnosis and suspicion of double intussusception intraoperatively and the surgical management is emphasized in this case report.